A survey for prevention of black hole attacks in wireless mobile adhoc networks using cryptographic techniques - Araghi, Tanya Koohpayeh (2013)
Since MANET is getting more ubiquitous, the need for offering sufficient security mechanisms in them seems noticeable. The security schemes measured in such networks are normally based on one or more of the subsequent cryptographic technologies such as symmetric-key cryptography, one way hash chain and digital signature. Black hole attack, is one of the most prevalent attacks in wireless mobile ad hoc networks. This paper is an overview on different cryptographic solutions proposed for prevention of black hole attacks in MANETs.